The Use of Percutaneous Lumbar Fixation Screws for Bilateral Pedicle Fractures with an Associated Dislocation of a Lumbar Disc Prosthesis - William D. Harrison; David J. Harrison (Case Reports in Orthopedics)
Study Design. Case report. Objective. To identify a safe technique for salvage surgery following complications of total disc replacement. Summary of Background Data. Lumbar total disc replacement (TDR) is considered by some as the gold standard for discogenic back pain. Revision techniques for TDR and their complications are in their infancy. This case describes a successful method of fixation for this complex presentation. Methods and Results. A 48-year-old male with lumbar degenerative disc disease and no comorbidities. Approximately two weeks postoperatively for a TDR, the patient represented with acute severe back pain and the TDR polyethylene inlay was identified as dislocated anteriorly. Subsequent revision surgery failed immediately as the polyethylene inlay redislocated intraoperatively. Further radiology identified bilateral pedicle fractures, previously unseen on the plain films. The salvage fusion of L5/S1 reutilized the anterior approach with an interbody fusion cage and bone graft. The patient was then turned intraoperatively and redraped. The percutaneous pedicle screws were used to fix L5 to the sacral body via the paracoccygeal corridor. Conclusion. The robust locking screw in the percutaneous screw allowed a complete fixation of the pedicle fractures. At 3-year followup, the patient has an excellent result and has returned to playing golf.